PHILOSOPHICAL MEANING BEHIND THE CHINESE CUISINE IN MANADO CITY - Martini, Sri; Suarka, I Nyoman; Cika, I Wayan; Setiawan, I Ketut (E-Journal of Cultural Studies, 2019)
The type of food served at lunar celebrations in Manado city has a distinctive flavor, color color, is seen to contain the meaning of Filososfis for the life of Chinese people. That is, which later became a fascination in this study. The purpose of this research is to uncover the Filofis meaning of the food sundries served in lunar celebrations. Data collection methods are performed with observations of participation and interviews in depth. Data analysis techniques are done qualitatively. The research conclusion that the type of food presented in the lunar celebration contains philosophical meaning for the human life of matching and related to the hope for goodness, the coming of fortune, prosperity, and health that is to be achieved by In the celebration, both individually and in the family. Keywords: Lunar celebrations, food offerings, philosophical meanings, good wishes